Hydrogen sulfide attenuates cardiac dysfunction in a rat model of heart failure: a mechanism through cardiac mitochondrial protection - Wang, Xianli (Portland Press Ltd., 2010)
HF (heart failure) after MI (myocardial infarction) is a major cause of morbidity and mortality worldwide. Recent studies have shown that hydrogen sulfide (H(2)S) has cardioprotective effects. Hence, we aimed to elucidate the potential effects of H(2)S on HF after MI in rats. The HF model after MI was made by ligating the left anterior descending coronary artery. HF groups and sham-operated groups of rats were treated with vehicle, sodium hydrosulfide (NaHS) or PAG (propagylglycine). Equal volumes of saline, 3.136 mg·kg(−1)·day(−1) NaHS or 37.5 mg·kg(−1)·day(−1) PAG, were intraperitoneally injected into rats for 6 weeks after operation. Survival, lung-to-body weight ratio and left ventricular haemodynamic parameters were measured. The protein and gene expression of Bcl-2, Bax, caspase 3 and cytochrome c were analysed by Western blotting and RT–PCR (reverse transcription–PCR). TUNEL (terminal deoxynucleotidyl transferase-mediated dUTP nick-end labelling) and EM (electron microscopy) were used to examine apoptosis of heart tissues. NaHS was found to improve the survival and lower the lung-to-body weight ratio. It increased the LVSP (left ventricular systolic pressure) and the maximum rate of pressure and decreased LVEDP (left ventricular end-diastolic pressure). Furthermore, NaHS promoted Bcl-2 protein and mRNA expression and demoted Bax, caspase 3 protein and mRNA expression in HF rats. We also showed that NaHS decreased the leakage of cytochrome c protein from the mitochondria to the cytoplasm. Histological observation by TUNEL and EM proved that NaHS inhibited cardiac apoptosis in HF hearts and improved mitochondrial derangements, but that PAG aggravated those indices. Hence, H(2)S has protective effects in HF rats.